PRAKTIK JUAL BELI DENGAN MENGGUNAKAN PERBUATAN (BA’I AL-MU’ATHAH) PADA SUPERMARKET MENURUT PERSPEKTIF ‘URF - nur fadilla, riszky rosa (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2021)
This study aims to determine the practice of buying and selling using actions (ba'i al-mu'athah) in supermarkets according to the 'urf perspective. The research method used in this research is library research with a qualitative approach. The data sources of this research, were collected from books and journals. Which were analyzed using the Miles and Huberman analysis method which included three lines, namely data reduction, data presentation and drawing conclusions or verification. The results of this study conclude that the practice of buying and selling using actions (ba'i al-mu'athah) in supermarkets is allowed based on the 'urf perspective. This practice is allowed on the basis of several opinions of fiqh scholars, such as the opinion of Madzhab Syafi'i ,some of Madzhab Syafi'iyah (Imam An-Nawawi), Madzhab Hanafi  and Madzhab Maliki . Although there are some scholars who allow this practice, there are also scholars who do not allow it, like the opinion of Madzhab Syafi'i.Keywords : Buy and Sell, Ba’i Al-Mu’athah and ‘Urf